Two Mezzogiornos - Hans-Werner Sinn; Frank Westermann (Center for Economic Studies and ifo Institute (CESifo), 2000)
The analogy between the economic problems of the Mezzogiorno region and East Germany has been initially contested by many authors. This paper argues that there are striking similarities in the two regions, in terms of the causes of their economic predicament. With an aggregate labour productivity of less than 60% relative to the rest of the country, both are true transfer economies, whose consumption exceeds production by far. Beyond locational disadvantages, the present paper identifies overdrawn wages, high social security spending and the Dutch disease problem as core reasons for the poor economic performance and discusses possible cures.
Keywords: 330